Assessment of wind power capacity credit in Morocco: Outlook to 2020. Issue 2 (April 2020) - El Karkri, Yassir; El Makrini, Aboubakr; El Markhi, Hassane; Lamhamdi, Tijani; El Moussaoui, Hassan
The present article focuses on the calculation of the wind capacity credit by integrating the Moroccan project on the wind energy of 1000 MW in 2020. After an introduction to the Moroccan Integrated Wind Energy Project, a wind capacity credit assessment program will be implemented on Matlab software including the whole information about "installed capacity, number of plants, failure rate, types of installed units, peak demand etc." This program will be used to calculate the safety rate of an electrical system as well as the capacity credit of Morocco's electricity production network. This section will be built in two phases: the first phase will examine the impact of TAZA wind farm with an installed power of 150 MW, while the second phase will focus on the generalization of this study on all the wind farms that will be injected to the Moroccan grid in 2020. The research provides conclusion according to comments and assessment of the impact of this electric energy integration based on the wind generation.